1,500 stretches the complete guide to flexibility and movement - Liebman, Hollis Lance (Black Dog & Leventhal Publishers, 2017)
Presents a collection of stretches organized by body part intended to offer pain relief, increased flexibility, and improvements to one's physical appearance.--